Fibre reinforced concrete containing waste coconut shell aggregate, fly ash and polypropylene fibre - R. Prakash; R. Thenmozhi; Sudharshan N. Raman; C. Subramanian (Revista Facultad de Ingeniería Universidad de Antioquia, 2020)
The aim of this study is to investigate the effect of polypropylene fibre addition into eco-concrete made with fly ash, an industrial by product, as partial cement replacement material, and coconut shell, an agricultural waste, as coarse aggregates, on the mechanical properties of the concrete. Two different mixes were developed, one with coconut shell only as coarse aggregates, and the other with the combination of both conventional aggregates and coconut shell as coarse aggregates. The cement content was replaced with class F fly ash at 10% by weight in the concrete mixes. The volume fractions of polypropylene fibres used in this study were 0.25%, 0.5%, 0.75% and 1.0%. The addition of polypropylene fibres slightly reduces the slump and density of coconut shell concrete. As the volume fraction of fibres increases, the compressive strength and modulus of elasticity of coconut shell concrete also increases by up to 0.5% of fibre volume fraction. The split tensile strength and flexural strength of coconut shell concrete were also enhanced with fibre addition. The addition of 0.75% and 1.0% volume fractions of polypropylene fibres slightly reduces compressive strength. Results of this study show that polypropylene fibres may be used in coconut shell concrete to improve the mechanical properties of the composite.